INFLUENCE OF NANOPARTICLES OF LEAD ON THE ORGANIZM OF SUSPICIOUS ANIMALS WHEN USING WATER WITH CONTENT OF SODIUM AND SUNPATE STEARATES - Fedoriv, O.E.; Kopach, O.E.; Melnyk, N.A.; Lototska, O.V.; Lototskyy, V.V. (World of Medicine and Biology, 2019)
In our time, the important and urgent problem is the influence of heavy metals on the organism of an animal and people. It is known that their presence in nature is a normal phenomenon. However, due to the active human activity, the concentration of various xenobiotics increases rapidly. Particular danger is lead compounds, which have a high ability to move on tropic chains and accumulate in different organs. At present, special attention is being given among scientists to questions about the impact on the body of nanomaterials of heavy metals and, including, of lead. In modern conditions, in various sources of water of economic, drinking and cultural and household water use, in addition to heavy metals, there are also significant amounts of surface-active substances, which include sodium stearates and potassium. The purpose of the study was to investigate the effect of lead nanoparticles on the background of water use of animals with sodium stearate and potassium stearate on the bone marrow and peripheral blood of white rats. Thus, with the combined effect of lead nanoparticles in a dose of 70 mg / kg and sodium and potassium stearates on the body of the experimental rats, there was a more significant increase in the bone marrow of the number of pro-myelocytes, rodenuclear and segmental neutrophils, lymphocytes, normo-cytes, and a more significant decrease in myelocytes and meta-mylocytes than with a separate effect of nanoparticles of lead. Lead nanoparticles against the background of drinking water of various compositions caused an increase in the number of rodenuclear neutrophils, eosinophils, monocytes, lymphocytes and a decrease in the number of segmental neutrophils in the blood of experimental animals. When introducing nanoparticles, there were phenomena of anisocytosis, pocillocytosis and hypochromia of red blood cells. In animals that consumed water with sodium stearate followed by oral administration of lead nanoparticles, the amount of leukocyte blood cells was significantly higher compared to animals that consumed water with potassium stearate.